Manajemen Pembelajaran Bahasa Arab Berbasis Bimbingan Konseling di Era Digital - Edi Putra Jaya; Afrus Nufrizal; Nanang Aria Sandika; Dedi Afrison; Sain, Zohaib Hassan (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2025)
This study aims to describe the implementation of Arabic language learning management based on counseling services at MTsN 6 Kerinci in the digital era. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation. The research informants consisted of Arabic language teachers, school counselors, and students. The findings reveal that integrating counseling services into Arabic language learning management enhances students’ motivation, self-confidence, and active participation in the learning process. The use of digital technology, such as online learning applications and communication media, further strengthens the effectiveness of collaboration between teachers and counselors. Supporting factors include teachers’ commitment, institutional support, and student engagement, while challenges involve limited time for counseling services and uneven digital skills among educators. This study concludes that developing Arabic language learning management based on counseling services is relevant to the demands of the digital era and serves as an innovative strategy to improve the quality of language learning in Islamic junior high schools.